Learning from the China model: What is in it for Vietnam's economic development? - Cheok, C.K.; Ping, L.P.; Hing, L.K. (2011)
Vietnam and China have had a long, if not always amicable, historical relationship. This relationship continued to be important even as Vietnam began its transition from a command economy to greater market orientation using the same strategy of pragmatic gradualism adopted by China when the latter began its own transition a decade before. As this strategy appears now to have lost momentum following the onset of the 2008 global financial crisis, Vietnam's economic planners, preparing the country's Socioeconomic Development Strategy for the new decade (2011-2020), have proposed new initiatives to achieve sustained growth. China's successful experiments, specifically with enterprise groups, special economic zones, and technology and industrial policies, again loom large among these proposed initiatives. To be successful, however, Vietnamese planners will need to be aware of the particular circumstances that favored China's experiments, to draw lessons from China's successes and failures, and to overcome the major challenges that Vietnam especially faces. These include, in comparison with China, a less competitive state enterprise sector, weaker implementation capacity at the subnational level, and pervasive corruption.